Validation study of the tactical-technical and social competencies of football players scale - Setic, R.; Kolenovic-Dapo, J.; Talovic, M. (Sportski Logos, 2017)
The aim of this paper is to assess the validity and reliability of the Tactical-Technical and Social Competencies of Football Players Scale (TTSCS). Overall 166 football players (N=81 seniors and 85 juniors) from several BiH Premier League clubs took part in the study. The average age of participants was M=21.14 (SD=4.91); the average age for junior players was M=17.23 (SD=0.49), while for seniors it was M=25.15 (SD=4.21). Principal component analysis revealed four factors which explain 78.78% of variance of specific competencies of football players. In accordance with item grouping, the first factor was labeled attacking tactical-technical competencies (ATTC); the second was labeled defensive-tactical competencies (DTC); third was labeled technical competencies (TC), while the fourth factor was labeled social competencies (SC). Instrument reliability was assessed on the basis of the internal reliability coefficient. Alpha coefficient values for the entire scale and for individual subscales are very high. Criterion validity of the TTSCS was assessed on the basis of its correlation with a measure of football players' self-efficacy. Correlations between self-efficacy and three competency measures range from moderate to low. In other words, there was no correlation only between self-efficacy and technical competencies scale. Results indicate that the TTSCS possesses adequate metric characteristics and can be used as a measure of specific player competencies.